(untitled) (Academia Science Repository, 2023)
The volume of industrial production and the change processes of industry-specific sectors during the years 2010-2022 were evaluated based on statistical analysis. The trends of their change are expressed in graphs. An econometric model based on trend models of total production and consumer goods production in Kashkadarya region’s industrial enterprises and the effect of industrial production on Kashkadarya region’s GDP was built, and forecasts were made on this basis. Conclusions and suggestions are given based on the conducted statistical analysis and forecasts.